Congresses of Velehrad - Madey, N. M. (Ukrai͏̈ns'ke relihijeznavstvo, 2002)
The desire for unity among Christians, called the popular term "ecumenism", has its origins. The split between the Byzantine and Catholic churches finally established itself in the minds of ordinary people after the Crusades and the capture of the Crusaders of Constantinople in 1204. Subsequent centuries were marked by unity competitions, but the Roman Catholic Church was the initiator of these competitions. In Catholic theology, all churches that were not under papal jurisdiction were considered to be objects of missionary activity. The result of such missionary unity was the deepening of the divide between the Catholic and Eastern churches. Segments of the latter proclaimed unity with Rome, beginning their existence as Uniate churches.